PERLINDUNGAN TERHADAP INDIKASI GEOGRAFIS (PRODUK YANG DISTERTAI NAMA TEMPAT) DALAM RANGKA HUKUM NASIONAL DAN HUKUM INTERNASIONAL (UINSI Samarinda, 2013)
A geographical indication is a sign used on goods that have a specific geographical origin and possess qualities or a reputation that are due to that place of origin. Most commonly, a geographical indication consists of the name of the place of origin of the goods. Agricultural products typically have qualities that derive from their place of production and are influenced by specific local factors, such as climate and soil. Whether a sign functions as a geographical indication is a matter of national law and consumer perception.Our Country rich of local products that consist the name of place. There are many example of goods which consist of the name of the place as like: Sarong Samarinda, Coto Makassar, Apel Malang, Dodol Garut etc. As a contracting party of World Trade Organization especially Trade Relate Intellectual Property Right, Indonesia hava regulation to protect the product, UU No. 15 Tahun 2001 tentang Merek and PP No. 51 Tahun 2007 tentang Indikasi Geografis.